Capillary Fragility Studies in Diabetes. Issue 5649 (12th April 1969) - Hart, A.; Cohen, H.
Abstract : A new method for the measurement of capillary fragility based on the time of appearance of petechiae under standardized conditions has been used to study 88 non-diabetics and 211 patients attending a diabetic clinic. In the former the capillary fragility increased with age. In the diabetic group 78 out of 195 patients had complications, and in all age groups these latter patients had more fragile capillaries. In general the capillary fragility was greater in patients taking insulin than in those taking antidiabetic tablets or on diet alone, and in the first group capillary fragility was greatest in those receiving more than 50 units daily and least in those receiving less than 25 units daily. Capillary fragility measurement by this method may be of value in assessment, prognosis, and studying the response to treatment in diabetes.